Use of zinc phosphate cement as a luting agent for Denzir™ copings: an in vitro study - Mondragon Eduardo; Söderholm Karl-Johan M; Garcea Ileana (BMC, 2003)
Abstract Background The clinical success rate with zinc phosphate cemented Procera crowns is high. The objective with this study was to determine whether CADCAM processed and zinc phosphate cemented Denzir copings would perform as well as zinc phosphate cemented Procera copings when tested in vitro in tension. Methods Twelve Procera copings and twenty-four Denzir copings were made. After the copings had been made, twelve of the Denzir copings were sandblasted on their internal surfaces. All copings were then cemented with zinc phosphate cement to carbon steel dies and transferred to water or artificial saliva. Two weeks after cementation, half of the samples were tested. The remaining samples were tested after one year in the storage medium. All tests were done in tension and evaluated with an ANOVA. Results Sandblasted and un-sandblasted Denzir copings performed as well as Procera copings. Storage in water or artificial saliva up to one year did not decrease the force needed to dislodge any of the coping groups. Three copings fractured during testing and one coping developed a crack during testing. The three complete fractures occurred in Procera copings, while the partly cracked coping was a Denzir coping. Conclusion No significant differences existed between the different material groups, and the retentive force increased rather than decreased with time. Fewer fractures occurred in Denzir copings, explained by the higher fracture toughness of the Denzir material. Based on good clinical results with zinc phosphate cemented Procera crowns, we foresee that zinc phosphate cement luted Denzir copings are likely to perform well clinically.